High resolution sequencing of hepatitis C virus reveals limited intra-hepatic compartmentalization in end-stage liver disease - Hedegaard, Ditte L.; Tully, Damien C.; Rowe, Ian A.; Reynolds, Gary M.; Bean, David J.; Hu, Ke; Davis, Christopher; Wilhelm, Annika; Ogilvie, Colin B.; Power, Karen A.; Tarr, Alexander W.; Kelly, Deirdre; et al. (Elsevier, 2017)
Background & Aims